2018
DOI: 10.31871/wjrr.7.4.8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Vitamin C Level and MMP-2 Serum with Premature Rupture of Membranes and Normal Pregnancy

Abstract: Background: One of the important problems in obstetrics is premature rupture of membranes. Incidence of premature rupture of membranes caused by multifactorial, including the factors of infection and nutrients of pregnant women that affect the elasticity of membranes. The aim of the study to investigate the relationship vitamin C level and MMP-2 serum with premature rupture of membranes and normal pregnancy. Methods: This research is cross sectional comparative study design. The research is in the Midwife Room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Research efforts are suggested to identify the prevalence and risks of insufficient plasma Vitamin C levels in individuals of all ages (including infants and children) and more diverse race/ethnicities. Pregnancy status is another area where research is advised, as needs may transiently increase during the progression of the pregnancy [59][60][61]. It is also recommended to investigate both low SES and those considered middle class, as this study identified both to be significant predictors for decreased Vitamin C. Further examination of Vitamin C insufficiencies in older adults is suggested as findings may not be applied to residents of long-term care facilities, a sector with known nutritional inadequacies that would also benefit from increased surveillance and treatment [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research efforts are suggested to identify the prevalence and risks of insufficient plasma Vitamin C levels in individuals of all ages (including infants and children) and more diverse race/ethnicities. Pregnancy status is another area where research is advised, as needs may transiently increase during the progression of the pregnancy [59][60][61]. It is also recommended to investigate both low SES and those considered middle class, as this study identified both to be significant predictors for decreased Vitamin C. Further examination of Vitamin C insufficiencies in older adults is suggested as findings may not be applied to residents of long-term care facilities, a sector with known nutritional inadequacies that would also benefit from increased surveillance and treatment [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Participants who acknowledged food insecurity (n = 1449, 14.1%) had higher percentages of insufficient Vitamin C levels (deficiency, hypovitaminosis, and inadequate) compared to those who denied food insecurity (n = 6158, 85.9%) [χ2 = 114. 59 Vitamin C intake also showed significant differences across the categories of plasma Vitamin C for both non-consecutive days [Day One intake: F = 134.43, df = 4, p ≤ 0.001; Day Two intake: F = 88.84, df = 4, p < 0.001]. Mean ranges of reported dietary intake of Vitamin C were 39.4 mg to 124.9 mg for the two days collected.…”
Section: Associations Between Sample Characteristics and Vitamin C Levelsmentioning
confidence: 96%